Student’s educational and occupational aspirations (study in batak karo and melayu deli cultural) - Suci Rahma Hanum; Muri Yusuf; Herman Nirwana (Fakultas Ilmu Pendidikan UNP)
Every students have educational and occupational aspirations. The factors affecting the educational and occupational aspirations of students are cultural and gender. Aims of this research were to examine the differences educational and occupational aspirations between male and female of Batak Karo and Melayu Deli students. The population were 823 and samples 268 students. The instrument used the educational aspiration scale (R= 0,853) and occupational aspirations scale (R= 0,852). The data were analyzed by using MANOVA. The result of this research shows that there is not significant the difference on educational and occupational aspirations between Batak Karo and Melayu Deli students, there was significant difference on educational and occupational aspirations between Batak Karo male and female students, there was significant differences on educational aspirations between Melayu Deli male and female students and there was not significant difference on occupational aspirations.